Auto-optimizing hydrogen evolution catalytic activity of ReS2 through intrinsic charge engineering - Zhou, Yao (2020)
Optimizing active electronic states responding to catalysis is of paramount importance for developing high-activity catalysts because thermodynamics itself may not favor forming an optimal electronic state. Setting the monolayer transition metal dichalcogenide (TMD) ReS2 as a model for the hydrogen evolution reaction (HER), we uncover that intrinsic charge engineering has an auto-optimizing effect on enhancing catalytic activity through regulating active electronic states. The experimental and theoretical results show that intrinsic charge compensation from S to Re-Re bonds could manipulate the active electronic states, allowing hydrogen to absorb the active sites neither strongly nor weakly. Two types of S sites exhibit the optimal hydrogen adsorption free energies (Δ GH*) of 0.016 and 0.061 eV, which are the closest to zero corresponding to the highest HER activity. This auto-optimization via charge engineering is further demonstrated by higher turnover frequency per sulfur atom of 1-10 s-1 and lower overpotential of -147 mV at 10 mA cm-2 than those of other TMDs through multiscale activation and optimization. This work opens an avenue in designing extensive active catalysts through intrinsic charge engineering strategy.